Expression Analysis of Cnidarian-Specific Neuropeptides in a Sea Anemone Unveils an Apical-Organ-Associated Nerve Net That Disintegrates at Metamorphosis - Zang, Hannah; Nakanishi, Nagayasu (Frontiers in Endocrinology, 2020)
Neuropeptides are ancient neuronal signaling molecules that have diversified across Cnidaria (e.g. jellyfish, corals and sea anemones) and its sister group Bilateria (e.g. vertebrates, insects and worms). Over the course of neuropeptide evolution emerged lineage-specific neuropeptides, but their roles in the evolution and diversification of nervous system function remain enigmatic particularly in Cnidaria. As a step towards filling in this knowledge gap, we investigated the expression pattern of a cnidarian-specific neuropeptide – RPamide – during the development of the starlet sea anemone Nematostella vectensis, using in situ hybridization and immunohistochemistry. We show that RPamide precursor transcripts first occur during gastrulation in scattered epithelial cells of the aboral ectoderm. These RPamide-positive epithelial cells exhibit a spindle-shaped, sensory-cell-like morphology and extend basal neuronal processes that form a nerve net in the aboral ectoderm of the free-swimming planula larva. At the aboral end, RPamide-positive sensory cells become integrated into the developing apical organ that forms a bundle of long cilia referred to as the apical tuft. Later during planula development, RPamide expression becomes evident in sensory cells in the oral ectoderm of the body column and pharynx, and in the developing endodermal nervous system. At metamorphosis into a polyp, the RPamide-positive sensory nerve net in the aboral ectoderm degenerates by apoptosis, and RPamide expression begins in ectodermal sensory cells of growing oral tentacles. In addition, we find that the expression pattern of RPamide in planulae differs from that of conserved neuropeptides that are shared across Cnidaria, indicative of distinct functions. Our results not only provide the anatomical framework necessary to analyze the function of the cnidarian-specific neuropeptides in future studies, but also reveal previously unrecognized features of the sea anemone nervous system – the apical organ neurons of the planula larva, and metamorphosis-associated reorganization of the ectodermal nervous system.